Sex-related differences in perceptual indices, serum cortisol and blood lactate responses to endurance exertion in competitive male and female athletes in a field setting - Sochacka, K.; Janusz, M.; Obminski, Z. (Journal of Kinesiology and Exercise Sciences, 2022)
Background: Boxing requires very high aerobic fitness from male and female practitioners, therefore, endurance exercises play an important role in the preparation to competition. One of the way for rating of the state of demanded physical adaptation is monitoring of biological responses to endurance training units. The aim of the study was to examine psycho-hormonal responses to a 10km cross-country run in male and female boxers. Material and methods: Twenty-four amateur adult boxers, 12 women and 12 men, of various weight categories, excluding heavyweight athletes, performed field a 10km run. Capillary blood was sampled in the morning at 8:00, 5 minutes prior to the run (11:00 am), and within 5 minutes after exercise. Plasma cortisol concentration (C) was determined using a commercial ELISA kit (IBL, GERMANY). Post-exercise blood lactate was determined with a Lactate Scout analyzer. Pre-run anticipatory stress (AS) was estimated on a numerical scale of 1 to 10 points, with the same tool used to measure the rating of perceived exertion (RPE). Results: Morning plasma cortisol levels in females (540±82 nM) and males (520±73 nM) did not differ significantly but the pre-and post-run levels were higher in females. Furthermore, males rather than females showed lower pre-exercise compared to post-exercise C levels, meaning that blood lactate level was significantly higher in males (6.3±1.1 mM) compared to that in females (5.4±0.7 mM). There were no significant differences between the sexes for AS and RPE. However, both perceptual parameters were slightly higher in females. Conclusion: Based on blood cortisol measurements and perceptual parameters it can be concluded that the psychophysiological cost of exercise is higher in female athletes, even in the case of non-competitive exercise.